2022
DOI: 10.1038/s41467-022-32920-x
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between SUMOylation and ubiquitylation controls DNA end resection by maintaining MRE11 homeostasis on chromatin

Abstract: DNA end resection is delicately regulated through various types of post-translational modifications to initiate homologous recombination, but the involvement of SUMOylation in this process remains incompletely understood. Here, we show that MRE11 requires SUMOylation to shield it from ubiquitin-mediated degradation when resecting damaged chromatin. Upon DSB induction, PIAS1 promotes MRE11 SUMOylation on chromatin to initiate DNA end resection. Then, MRE11 is deSUMOylated by SENP3 mainly after it has moved away… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…MRE11A is SUMOylated following DSB generation [ 44 , 59–61 ]. SUMOylation stabilises MRE11A by preventing its ubiquitination and degradation [ 61 ]. SUMOylation also stabilises the NBS1 interactor hSSB1 (single-stranded DNA-binding protein 1) enhancing ATM recruitment to DSBs [ 62 ].…”
Section: Dna End Resectionmentioning
confidence: 99%
“…MRE11A is SUMOylated following DSB generation [ 44 , 59–61 ]. SUMOylation stabilises MRE11A by preventing its ubiquitination and degradation [ 61 ]. SUMOylation also stabilises the NBS1 interactor hSSB1 (single-stranded DNA-binding protein 1) enhancing ATM recruitment to DSBs [ 62 ].…”
Section: Dna End Resectionmentioning
confidence: 99%
“…Hence, this study demonstrated that MRE11 SUMOylation, in tandem with UB, is dynamically controlled by PIAS1 and SENP3 to facilitate DNA end excision and maintain genomic stability. 67 However, in contrast to studies of MRE11 phosphorylation, further in‐depth studies into MRE11 UB and ubiquitin‐like modifications (UBLs) are urgently needed (Figure 4B ).…”
Section: The Mrn Complex In Hrmentioning
confidence: 99%